2021
DOI: 10.1182/bloodadvances.2021005096
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic modeling of factor concentrates in hemophilia: an overview and evaluation of best practice

Abstract: The accuracy of pharmacokinetic (PK)-guided dosing depends on the clinical and laboratory data used to construct a population PK model, as well as the patient's individual PK profile. This review provides a detailed overview of data used for published population PK models for factor VIII (FVIII) and factor IX (FIX) concentrates, to support physicians in their choices which model best suits each patient. Furthermore, to enhance detailed data collection and documentation, we do suggestions for best practice. A l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Hence, using an incorrect tool for a particular PK evaluation may lead to unreliable outcomes. [141][142][143] Applications for patient diaries like haemtrack, HaemoAssist 2, smart medication, florio HAEMO, and myPKFiT have been devised to enable patients to record bleeding events and administered doses. These applications can also notify patients when they reach critical factor levels to prevent missed FVIII infusions.…”
Section: Other Concerns Regarding Current Hemophilia a Treatment Impl...mentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, using an incorrect tool for a particular PK evaluation may lead to unreliable outcomes. [141][142][143] Applications for patient diaries like haemtrack, HaemoAssist 2, smart medication, florio HAEMO, and myPKFiT have been devised to enable patients to record bleeding events and administered doses. These applications can also notify patients when they reach critical factor levels to prevent missed FVIII infusions.…”
Section: Other Concerns Regarding Current Hemophilia a Treatment Impl...mentioning
confidence: 99%
“…Depending on PK for bleeding control may be unreliable if the standard of home monitoring is unsatisfactory. 143 PK analysis could be used to recognize patients with extended FVIII half-lives, enabling them to lessen their dosage and/or dosing frequency. This will eventually reduce treatment costs and be more convenient for children, older people, and others with poor venous access.…”
Section: Other Concerns Regarding Current Hemophilia a Treatment Impl...mentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 However, data from controlled clinical trials are limited, and information on the benefit of targeting higher FVIII trough levels has therefore been derived from a modeling approach. [19][20][21][22][23] The recent phase 3, prospective, randomized, open-label, multicenter PROPEL study (NCT02585960) evaluated the safety and efficacy of the EHL recombinant FVIII rurioctocog alfa pegol at two PK-guided target FVIII trough level ranges (1-3% and 8-12%). This study demonstrated that a higher proportion of patients achieved zero bleeds when an elevated FVIII trough level was targeted.…”
Section: Introductionmentioning
confidence: 99%